2020
DOI: 10.3390/life10030026
|View full text |Cite
|
Sign up to set email alerts
|

Circumnutation and Growth of Inflorescence Stems of Arabidopsis thaliana in Response to Microgravity under Different Photoperiod Conditions

Abstract: Circumnutation is a periodic growth movement, which is an important physiological mechanism of plants to adapt to their growth environments. Gravity and photoperiod are two key environmental factors in regulating the circumnutation of plants, but the coordination mechanism between them is still unknown. In this study, the circumnutation of Arabidopsis thaliana inflorescence stems was investigated on board the Chinese recoverable satellite SJ-10 and the Chinese spacelab TG-2. Plants were cultivated in a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Therefore, FT and SOC1 could integrate spaceflight-related stimuli into the pathways that regulate flowering [ 230 ]. However, in another experiment by the same group, plants uploaded to the space lab after they had already reached the rosette stage showed no such delay [ 231 ]. In contrast, growth experiments in the Japanese Kibo module on the ISS describe a mostly normal development of Arabidopsis under microgravity conditions [ 232 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, FT and SOC1 could integrate spaceflight-related stimuli into the pathways that regulate flowering [ 230 ]. However, in another experiment by the same group, plants uploaded to the space lab after they had already reached the rosette stage showed no such delay [ 231 ]. In contrast, growth experiments in the Japanese Kibo module on the ISS describe a mostly normal development of Arabidopsis under microgravity conditions [ 232 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spaceflight experiments were conducted in a Plant Culture Box (PCB), which provides atmospheric, temperature, and hydration monitoring and control for the plant growth in the long term (the seed-to-seed experiment) as described by Wang et al (2018) and Wu et al (2020) [ 9 , 46 ]. Briefly, the PCB consists of five culture chambers (CCs), including two CCs under short-day (SD, 8 h light /16 h dark) and three CCs under long-day (LD, 16 h light/8 h dark) conditions ( Figure 1 A–D).…”
Section: Methodsmentioning
confidence: 99%
“…Various environmental stresses, such as drought, salt and temperature, were reported to have interfered with flowering (Galbiati et al, 2016;Fernández et al, 2016). Spaceflight is a novel stress to plants, which evolved on Earth (Hampp et al, 1997;Zheng et al, 2008;Paul et al, 2017;Wu et al, 2020). Previous studies indicated that spaceflight is a compound stress, imposing multiple constraints on plants by integration of spaceflight conditions.…”
Section: Discussionmentioning
confidence: 99%